Analisis Pajak Penghasilan Pasal 23 Dan Pasal 25 Terhadap Wajib Pajak Badan CV PRR - Kania, Niken Yofi; Sulistyowati, Erna (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Taxes become a primary source of income for the state to be used as expenses that fund infrastructure development, education, culture, health, and other aspects that benefit society. Income tax under Income Tax Article 23 is a tax collected/withheld by third parties on income from rent or services, as well as other income not subject to Income Tax Article 21. Meanwhile, income tax under Income Tax Article 25 applies a self-collection system for taxpayers to calculate, pay, and report the outstanding tax on income earned from their business activities. This analysis is conducted to determine whether CV PRR has made timely payments and reports for under Income Tax Article 23 and 25, as well as to understand how the calculations for under Income Tax Article 23 and 25 are done. The research results show that CV PRR has made timely payments and reports, and the calculations have been in line with the prevailing tax regulations.